Prevalence of bacterial burden on macroscopic contaminants of orthopaedic surgical instruments following sterilization. (December 2022) - Wellington, I.J.; Schneider, T.J.; Hawthorne, B.C.; McCarthy, M.B.; Stelzer, J.W.; Connors, J.P.; Dorsey, C.; Williams, V.; Lindsay, A.; Solovyova, O.
Summary: Background: Macroscopic contamination of orthopaedic instruments with particulates, including cortical bone and polymethyl methacrylate (PMMA) bone cement, that have previously undergone pre-operative sterilization is frequently encountered peri- or intraoperatively, calling into question the sterility of such instruments. Aim: To determine if macroscopic contaminants of orthopaedic surgical instrumentation maintain a bacterial burden following sterile processing, and to determine the most commonly contaminated instruments and the most common contaminants. Methods: Macroscopic contaminants in orthopaedic instrument trays were collected prospectively at a single tertiary referral centre over a 6-month period from August 2021 to May 2022. When identified, these specimens were swabbed and plated on sheep blood agar. All specimens were incubated at 37 °C for 14 days, and inspected visually for colony formation. When bacterial colony formation was identified, samples were sent for species identification. Results: In total, 33 contaminants were tested, and only one contaminant was found to be growing bacterial colonies ( Corynebacterium sp.). The items most commonly found to have macroscopic contamination were surgical trays ( N =9) and cannulated drills ( N =7). The identifiable contaminants were bone ( N =10), PMMA bone cement ( N =4) and hair ( N =4). Eleven macroscopic contaminants were not identifiable. Conclusion: This study found that 97% of macroscopic orthopaedic surgical instrument contaminants that underwent sterile processing did not possess a bacterial burden. Contaminants discovered during a procedure are likely to be sterile, and do not pose a substantially increased risk of infection to a patient.